2020
DOI: 10.1097/qai.0000000000002313
|View full text |Cite
|
Sign up to set email alerts
|

Increased Mortality With Delayed and Missed Switch to Second-Line Antiretroviral Therapy in South Africa

Abstract: Background. After failure of first-line antiretroviral therapy (ART) in the public sector, delayed or missed second-line ART switch is linked with poor outcomes in patients with advanced HIV. Setting:We investigated delayed or missed second-line ART switch following confirmed virologic failure in the largest private sector HIV cohort in Africa.Methods. We included HIV-infected adults with confirmed virologic failure after six months of non-nucleoside reverse-transcriptase inhibitor-based ART. We estimated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…In short, routine VL monitoring reduces mortality when used together with adherence support [ 48 ] and a timely switch to effective treatment [ 49 , 50 ], but ensuring coverage of VL and second-line ART for those with a diagnosis of virological failure remains a huge challenge. When coverage is low, the overall benefit from VL scale-up might be lower than anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…In short, routine VL monitoring reduces mortality when used together with adherence support [ 48 ] and a timely switch to effective treatment [ 49 , 50 ], but ensuring coverage of VL and second-line ART for those with a diagnosis of virological failure remains a huge challenge. When coverage is low, the overall benefit from VL scale-up might be lower than anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…Our study observed a mortality rate of 3.9/100PYS for those who did not have a treatment modification, and 3.0/100PYS for those who did without ART interruption. Delayed switch from first-line to second-line ART has been shown to be associated with increased mortality in resource-limited settings [26,27]. This study observed no differences in survival outcomes after second-line ART failure, however, the benefits of treatment modification were seen with greater CD4 increase in those who had their treatment modified without interruption, while those who had treatment interruption were less likely to achieve undetectable VL compared with those who remained on the same failing second-line regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Third, among people with confirmed viral failure, a systematic review, 26 and more recent individual studies, 4 27-29 have found that only 30%-60% are switched to second-line ART. Even among patients who are switched, this can take a further 3-12 months, [27][28][29] with delays of even a few months being associated with increased risk of opportunistic infections and mortality, particularly among people with low CD4 counts. 1 4 27-29 Taken together, these data highlight the need for interventions to reduce delays and improve the management of viraemia.…”
Section: Problems With Management Of Viraemiamentioning
confidence: 99%